2010
DOI: 10.3109/17483101003718161
|View full text |Cite
|
Sign up to set email alerts
|

An affordable, computerised, table-based exercise system for stroke survivors

Abstract: A low-cost device has been developed which increases the exercise of gravity supported reaching movements, provides goal-directed tasks with rewards and motivates the user to undertake extended rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…In comparison, Lewis et al found that for some participants, challenging themselves during computer-based games and observing progress through levels of difficulty and real-time score feedback meant encouragement to continue trying [32]. Some authors consider providing a score following the playing of a computer game important, because scores and similar feedback allow for performance feedback, which promotes learning [14,33].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Lewis et al found that for some participants, challenging themselves during computer-based games and observing progress through levels of difficulty and real-time score feedback meant encouragement to continue trying [32]. Some authors consider providing a score following the playing of a computer game important, because scores and similar feedback allow for performance feedback, which promotes learning [14,33].…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest advantages of the VR-based programs was to maximize the effects of exercise by triggering players' interest in being fully immersed in the games, compared to other exercise programs 33) . Moreover, as the game continued, the score was displayed to give instant feedback, which fostered an interest in competing for a better score.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 123 were discarded since they did not fulfil the inclusion criteria: Seven papers were not written in English, three were book chapters, 112 were not related to shoulder rehabilitation. A total of 12 articles remained relevant for inclusion, corresponding to nine different AR-based systems for shoulder rehabilitation (see Figure 1): NeuroR [18], ARS [19], RehaBio [20], MirrARbilitation [21,22], ARIS [23,24], AR Games by De Leon et al [25], SleeveAR [26,27], AR Fruit Ninja [28], AR System by Colomer et al [29]. The following section presents an overview of the AR-based reviewed systems for shoulder rehabilitation, as well as an analysis and discussion of their technical and clinical aspects.…”
Section: Overview Technical and Clinical Aspects Of Ar-based Systemsmentioning
confidence: 99%
“…ARS [19] (Figure 1, top-center) is a simple AR system for home rehabilitation after stroke. The system uses AR technology to provide a motivational environment, based on a "butterfly catching" game, to perform reaching tasks.…”
Section: Overviewmentioning
confidence: 99%